Silver for entertaining the Ickworth collection - Rothwell, James (PWP, 2017)
One of the most important collections of eighteenth-century silver in Europe is to be found at Ickworth House in Suffolk. It extends to nearly a thousand pieces, is of the highest quality, style and exuberance of form and survives virtually intact along with extensive and previously untapped archival evidence of its commissioning and use, and of the diplomatic, political and court appointments of its principal patron, George William Hervey, 2nd Earl of Bristol. The finest London makers of the time are represented including Paul de Lamerie, Paul Crespin and, in particular, Frederick Kandler, and it also contains a significant quantity of continental pieces, commissioned contemporaneously whilst Lord Bristol was in Turin. It was in part by maintaining a sufficient state of magnificence there, and in Madrid, that the Earl could hold the diplomatic ground for Britain during the Seven Years War and his silver, of the latest French fashions and of opulent extent, was a critical tool in his armoury. This book, which will be lavishly illustrated, will analyse the individual objects from stylistic and technical perspectives, and use them to shed light on the patronage, fashion and social history of a vibrant and turbulent era of European history
Keywords: Hervey, Frederick -- 1730-1803; Geschichte 1680-1860; Privatsammlung; Tafelsilber; Ickworth House -- Ickworth; Katalog